2006
DOI: 10.1021/bi060360k
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Analysis of γ‘ Peptide (410−427) Interactions with Thrombin Anion Binding Exosite II

Abstract: Thrombin utilizes two anion binding exosites to supplement binding of fibrinogen to this serine protease. Approximately 7-15% of the fibrinogen gamma chain exists as the highly anionic gamma' variant (408VRPEHPAETEY(S)DSLY(S)PEDDL427). This segment has been demonstrated to target thrombin ABE-II and can accommodate sites of phosphorylation in place of sulfonation without sacrificing binding affinity. The present work employed 1D and 2D solution NMR to characterize the structural features of the bound gamma' pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
112
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(120 citation statements)
references
References 55 publications
(117 reference statements)
6
112
1
Order By: Relevance
“…In addition, modest protection could at times be documented for the thrombin fragments 85-99 and 135-149D. Previous HDX studies also reported effects on these three thrombin fragments (15,28). The solvent protection observed for thrombin fragments 173-180 and 173-181 in the presence of PPACK was further maintained upon the addition of Hirudin(54 -65).…”
Section: Monitoring Shifts In Hdx Centroids In Presence Of Ligand-mentioning
confidence: 79%
See 4 more Smart Citations
“…In addition, modest protection could at times be documented for the thrombin fragments 85-99 and 135-149D. Previous HDX studies also reported effects on these three thrombin fragments (15,28). The solvent protection observed for thrombin fragments 173-180 and 173-181 in the presence of PPACK was further maintained upon the addition of Hirudin(54 -65).…”
Section: Monitoring Shifts In Hdx Centroids In Presence Of Ligand-mentioning
confidence: 79%
“…4) verified that ligand binding to ABE II is not dependent on the presence of an intact ABE I. Prior NMR studies on the binary fibrinogen ␥Ј(410 -427) to ␥-thrombin complex could only demonstrate that thrombin contact sites were maintained in the presence of a species with a disrupted ABE I (15). The current HDX studies on ␥-thrombin revealed that the GpIb␣ and fibrinogen ␥Ј ligands were still protecting ABE II from hydrogen-deuterium exchange (see Fig.…”
Section: Monitoring Shifts In Hdx Centroids In Presence Of Ligand-mentioning
confidence: 91%
See 3 more Smart Citations